The Influence of Music on Language Development - Bojanc, Anže (Širjenje obzorij o poučevanju glasbe, 2025)
This chapter examines studies on the impact of music on children's language learning. The inclusion of music in the educational activities of primary school children positively influences their language achievement, particularly for children learning English as a second language. The results indicate that the regular use of songs and musical activities contributes to improved language skills and correct pronunciation, as pupils develop the ability to read in two languages, demonstrating an effective connection between music and language. Additional studies reveal that selecting songs with positive lyrics fosters a positive emotional state, which, in turn, enhances motivation for language learning.